2003
DOI: 10.1088/0953-2048/16/9/315
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and superconducting properties of PIT-processed MgB2wire after heat treatment

Abstract: The mechanical and superconducting properties of MgB 2 wires heat treated at various conditions have been investigated. Superconducting MgB 2 wires, fabricated by the powder-in-tube (PIT) method, show a transition temperature T c at 32.4 K for the as-rolled wire as shown by dc-resistivity measurement. It is found that the T c is improved (37.3-38.4 K) by subsequent Ar annealing treatment under various sintering temperatures and times. Remarkably, the annealed samples show significant improvement in the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
(26 reference statements)
2
21
2
Order By: Relevance
“…The peak of the f p curves takes place at b peak ϳ 0.2 for all samples, which seems to be intrinsic to bulk MgB 2 . This position of the peak has been observed in MgB 2 in many other works [13][14][15][16][17] and also in some LTSs, such as the A-15 Nb 3 Sn ͑Refs. 18-20͒ and the Chevrel-phase PbMo 6 S 8 , 21 characterized by F p ϰ b 1/2 ͑1−b͒ 2 .…”
Section: Flux Pinning Curvessupporting
confidence: 78%
See 1 more Smart Citation
“…The peak of the f p curves takes place at b peak ϳ 0.2 for all samples, which seems to be intrinsic to bulk MgB 2 . This position of the peak has been observed in MgB 2 in many other works [13][14][15][16][17] and also in some LTSs, such as the A-15 Nb 3 Sn ͑Refs. 18-20͒ and the Chevrel-phase PbMo 6 S 8 , 21 characterized by F p ϰ b 1/2 ͑1−b͒ 2 .…”
Section: Flux Pinning Curvessupporting
confidence: 78%
“…20,21 The values of m = 1.6-2.1 have also been obtained in MgB 2 superconductor by another group. 14 The flux-line shear mechanism has been studied in detail and several authors proposed the expressions for F p based on the flux-lattice shearing. Kramer derived an expression for the pinning force, F p ϰ b 1/2 ͑1−b͒ 2 , assuming that the flux motion occurs by synchronous shear of the flux lattice around the line pins that are too strong to allow local depinning of the magnetic flux: Although the predicted function F p ϰ b 1/2 ͑1−b͒ 2 is observed in many superconductors, this formula has two main drawbacks, since it predicts a weak dependence on the grain size, which is in disagreement with experimental observations, 5,18,19 and it uses an expression for c 66 , which is only valid at high fields, 1 − b Ӷ 1.…”
Section: Flux Pinning Curvesmentioning
confidence: 99%
“…It has been widely reported that a reaction layer forms during heat treatment at the Fe/MgB 2 interface in wires and tapes prepared both by the in situ [36][37][38][39] and the ex situ [40][41][42][43][44][45] preparation routes.…”
Section: Fe 2 B Formationmentioning
confidence: 99%
“…In addition, the critical current density for the silver added samples are improved as compared to the silver free sample, where the sample added 5 wt% of silver showed highest critical current density 40 kA/cm 2 at 20 K. These values are very low as compared to the present results which clearly indicates that both optimum silver content and optimum sintering temperature are crucial to get high performance bulk MgB 2 material. Similarly, improvements had reported that Ag doping significantly enhances MgB 2 formation rate in MgB 2 wires with enhanced properties [22]. On the other hand, these results indicate that Ag addition to MgB 2 can be one of the ways to improve not only mechanical properties [17,[21][22][23][24] but also flux pinning; the critical temperature remains almost unchanged.…”
Section: Magnetization Experimentsmentioning
confidence: 74%
“…Similarly, improvements had reported that Ag doping significantly enhances MgB 2 formation rate in MgB 2 wires with enhanced properties [22]. On the other hand, these results indicate that Ag addition to MgB 2 can be one of the ways to improve not only mechanical properties [17,[21][22][23][24] but also flux pinning; the critical temperature remains almost unchanged. It is also positive that Ag does not react with MgB 2 and can help to reduce cracks density like in cuprates [25].…”
Section: Magnetization Experimentsmentioning
confidence: 74%